Maternal Sepsis 2010: Early Recognition and Aggressive Treatment with Early Goal Directed Therapy can Improve Maternal Outcomes - Ann Guinn, Debra (Current Women's Health Reviews, 2011)
Maternal sepsis remains a major preventable cause of morbidity and mortality worldwide. The current epidemic of obesity, diabetes, and cesarean delivery will most certainly increase the risk of infectious morbidity and mortality. Women who undergo cesarean are three times more likely to develop sepsis. Early recognition of cases and prompt treatment are essential to improve outcomes. Most cases of maternal sepsis are due to direct obstetrical causes and should be treated with broad spectrum antibiotics and source control measures. Early goal directed therapies should be initiated according to standardized protocols. Patients should be transferred to a critical care unit if feasible. Optimal care for the septic patient requires a multidisciplinary team with expertise in all relevant areas including critical care, infectious disease, maternal fetal medicine, obstetrics, anesthesia, pharmacology, and neonatology. This article reviews the epidemiology, microbiology, pathophysiology and treatment of obstetrical sepsis.
Keywords: cesarean delivery